Effect of Alkali Lignin on Laccase Activity and Mycelial Biomass of Flammulina velutipes - Mei-Ling Han; Yi-Lin Zhao; Tian-Yu Liu; Lu-Sen Bian; Zi-Han Li; Ming-Xue Li; Jia Li; Xiao-Qi Yang; Qi An (BioResources)
The effect of alkali lignin on laccase activity and mycelial biomass of Flammulina velutipes was investigated under different fermentation temperature. The secretion of laccase by F. velutipes has certain specificity. Specifically, laccase activity could not be detected by F. velutipes CCMSSC 00103 under most fermentation medium, but could be detected by F. velutipes FL 19 under more fermentation medium. Among the three strains of F. velutipes, the laccase secretion capacity of F. velutipes FL 19 was obviously better than that of F. velutipes CCMSSC 05331 and F. velutipes CCMSSC 00103. Maximum laccase activity with the value of 73.42 ± 4.74 U/L was secreted by F. velutipes FL 19 in fermentation medium 2 appeared at 2th day. The presence of alkali lignin was useful for improving laccase activity secreted by F. velutipes and the effect of alkali lignin on improving laccase activity exceeded that of Populus beijingensis. F. velutipes were more suitable for secreting laccase at 26 ℃ due to the maximum laccase activity measured at 26 ℃ (73.42 ± 4.74 U/L) higher than that measured at 33 ℃ (70.71 ± 6.89 U/L). The results were useful for selecting suitable medium and temperature of F. velutipes strains to produce low-cost laccase.